The Prophetic Education Paradigm as the Scientific Integration of UIN Saifuddin Zuhri in Merdeka Belajar Policy - Moh. Roqib; Agus Husein As Sabiq (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
This study aims to determine the prophetic education paradigm as an approach of scientific integration in the State Islamic University of Prof. KH. Saifuddin Zuhri Purwokerto (UIN Saizu) in the